Anti-Exceptionalism about Logic and the Burden of Explanation. Issue 8 (2nd November 2021) - Martin, Ben
Abstract: Considerable attention recently has been paid to anti-exceptionalism about logic (AEL), the thesis that logic is more similar to the sciences in important respects than traditionally thought. One of AEL's prominent claims is that logic's methodology is similar to that of the recognised sciences, with part of this proposal being that logics provide explanations in some sense. However, insufficient attention has been given to what this proposal amounts to, and the challenges that arise in providing an account of explanations in logic. This paper clarifies these challenges, and shows how the practice-based approach is best placed to meet them.